Remarriage of elderly Widows: Widows’ attitude and fear regarding new romantic relationships - Motsoeneng, Molefi (Technium Social Sciences Journal, 2021)
This study examines the fears, after the death of their partners, which elderly widows experience regarding a new romantic relationship, in other words the decision whether to stay single or remarry. Participants in the study were widows who provided information about their attitude and fears regarding remarriage. The study operationalizes the theory of marriage in order to understand the factors that influenced their decisions whether to remain single or opt for re-marriage. The study is anchored in a phenomenological approach. Semi-structured interviews with elderly widows who were not currently married were employed to collect data. The data were analyzed using thematic content analysis that defined the experiences and perceptions of elderly widows. The findings were categorized into five main themes: fear of being ostracised by in-laws and family pressure, poor previous marriages, the caregiver role, inheritance rights, and not being able to find a suitable partner. Their involvement in a remarried relationship is perceived as taboo by both family and family-in-law. Furthermore, they see a remarriage as compromising their inheritances rights and are aware of the difficulty of finding a partner who matches their preference.